2012
DOI: 10.1021/bi201433h
|View full text |Cite
|
Sign up to set email alerts
|

Active Site Substitution A82W Improves the Regioselectivity of Steroid Hydroxylation by Cytochrome P450 BM3 Mutants As Rationalized by Spin Relaxation Nuclear Magnetic Resonance Studies

Abstract: Cytochrome P450 BM3 from Bacillus megaterium is a monooxygenase with great potential for biotechnological applications. In this paper, we present engineered drug-metabolizing P450 BM3 mutants as a novel tool for regioselective hydroxylation of steroids at position 16β. In particular, we show that by replacing alanine at position 82 with a tryptophan in P450 BM3 mutants M01 and M11, the selectivity toward 16β-hydroxylation for both testosterone and norethisterone was strongly increased. The A82W mutation led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 45 publications
4
62
1
Order By: Relevance
“…On the basis of the results presented here, it appears that during the entrance into and binding of testosterone and androstenedione to the active site, the presence of Ala at position 206 may lead to a distortion or twisting of the D-ring of both testosterone and androstenedione that reorients the 16a face toward the heme iron. This finding is in agreement with a previous study using the A82W P450 mutant of CYPBM3 as a tool for the regioselective hydroxylation of testosterone at the 16b position (Rea et al, 2012). It is interesting to note that aromatic residues (Paine et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…On the basis of the results presented here, it appears that during the entrance into and binding of testosterone and androstenedione to the active site, the presence of Ala at position 206 may lead to a distortion or twisting of the D-ring of both testosterone and androstenedione that reorients the 16a face toward the heme iron. This finding is in agreement with a previous study using the A82W P450 mutant of CYPBM3 as a tool for the regioselective hydroxylation of testosterone at the 16b position (Rea et al, 2012). It is interesting to note that aromatic residues (Paine et al, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…In this context, enzymatic steroid hydroxylation catalyzed by engineered P450 mutants (e.g., of BM3) has gained attention for the preparation of diverse and unique hydroxylated steroids with pharmacological activity 8. ‐9 However, the use of isolated P450 for larger‐scale application is hampered by low activity, catalytic efficiency, and stability outside cells, the requirement for NAD(P)H (as electron donating co‐substrate), and the necessity for electron‐transferring partners 10…”
Section: Introductionmentioning
confidence: 99%
“…[9] We have also shown that restriction of the active site of BM3 mutant M01 by replacing an alanine at position 82 with tryptophan resulted in selective hydroxylation of TES on the D ring at the 16 b-position. [10] However, D-ring hydroxylation of TES by P450 BM3 mutants has been reported only on its b face until now. The regio-and stereoselectivity of P450-mediated reactions depend upon the orientation of the substrate relative to the reactive iron-oxo species, which is in turn determined by the active-site configuration of the P450 enzyme.…”
mentioning
confidence: 99%